Internet use and well-being of young adults - Techatassanasoontorn,A.A. (2015)
Internet has significantly transformed how, when and where people conduct their everyday life activities. This study examines the relationship between Internet use and well-being. We ask: how do Internet use and the quality of Internet and non-Internet experiences influence well-being? Drawing on the subjective well-being literature in economics and psychology as well as empirical research on Internet use and impacts, we evaluate the influence of domain life satisfaction and affective experiences associated with Internet and non-Internet activities on life satisfaction. Young adults in Thailand are the empirical focus of this study. The results suggest that satisfaction with family is important to their life satisfaction. Positive affect from Internet activities is important to a satisfying life of young adults. They appear to value positive affect from Internet activities more than positive affect from non-Internet activities. On the other hand, negative affect from both Internet and non-Internet activities decreases life satisfaction. © (2013) by the AIS/ICIS Administrative Office. All rights reserved.